Flat Stanley Plays Ball - Brown, Jeff; Mitchell, John (London Egmont, 2016)
When Stanley Lambchop joins the rounders team, he discovers that being flat can help him play. But not everyone thinks that flat players should be allowed... The Reading Ladder series helps children to enjoy learning to read. It features well-loved authors, classic characters and favourite topics, so that children will find something to excite and engage them in every title they pick up. It's the first step towards a lasting love of reading
English stories
Level 1
2 13
Keywords: English stories